The Characteristics Of Shoreface Deposits And The Reservoir Implication Of Seulimum Formation, Aceh Besar - Hidayat Syah Putra; Rifqan Rifqan; Akmal Muhni; Dewi Sartika (Jurnal Geosains dan Teknologi, 2021)
The shoreface deposits study commonly conducted to characterize the reservoir's physical properties carried out by surface geological data. The physical properties focused on pore space conditions controlled by sedimentary process and tectonic settings in Seulimum Formation. The method used as descriptive analysis and previous study of the area interested. The geological data showed shoreface environmental deposits that can be divided into two types of environmental deposits they are middle shoreface and upper shoreface deposits. These environmental deposits are proven by some features such as bioturbation with an abundant presence of Ophiomorpha in the second stop sites (total 5 stop sites). The first stop site indicates two kinds of environmental deposits by coarse sandstones and mudstones dominated facies presence in the specific beds. Mudclast and hummocky structures also present in the field observation that concludes complex environmental deposits during the quaternary period the formation. Based on characteristics of facies could suggest those sediment products deposited on shallow marine. These wave-dominated coasts generally have an excellent reservoir potential effect on shoreface sands that are laterally continuous and were orientated parallel to the shoreline.